Pembinaan Kepala Sekolah Dalam Upaya Meningkatkan Mutu Pendidikan - Nursyifa, Aulia; E, Nurzaman (FKIP Universitas Pamulang, 2019)
Improved quality of education viewed from quality human resources are there in the school. The principal plays an important role as a leader in fostering and developing the educational personnel and educators at the school. In the task given there are problems faced include a lack of understanding of the principal duties and responsibilities which should be exercised especially that has been set in the regulation, resulting in the role of principal yet to a maximum in terms of managerial, entrepreneurial development, and supervision at the school. This devotion uses the method of community education in the form of workshops aimed at improving the understanding of the principal about duties and responsibilities in the school. The results of the public service can be seen from enthusiastic participants in the workshop as well as a series of events following an increase in understanding of the principal of duty as head of the school. Based on the results of such devotion can be concluded that an increase in the professional head of the school is very influential on the quality of produce educators and educators at the school. This devotion activity expected to be undertaken on an ongoing basis so that it can intertwine cooperation Work Conference is the principal (MKKS) South Tangerang.